Workshop in Borana, Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Workshop in Borana, Ethiopia. Part of the project: Playing out transformative adaptation in the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) sites in East Africa. Photos: Anton Eitzinger (CIAT)